Association between chemotherapy-related cardiac dysfunction (CTRCD) and 6-minute walking distance (6MWD) in breast cancer patient receiving anthracycline-based chemotherapy - Putri Ayudhia Trisnasari; Irsad Andi Arso; Hasanah Mumpuni; Vita Yanti Anggraeni; Susanna Hilda Hutajulu; Mardiah Suci Hardianti; Hartopo, Anggoro Budi (Published by Universitas Gadjah Mada, 2024)
Anthracycline chemotherapy is one of the most commonly given therapies to breast cancer patients. Anthracycline has a cardiotoxicity effect causing cardiac myocyte death. This chemotherapy-related cardiac dysfunction (CTRCD) will decrease oxygen delivery to tissues characterized by reduced cardiorespiratory fitness. The 6-min walking distance (6MWD) could be a predictor of cardiorespiratory fitness. This study aimed to investigate the association between CTRCD and the reduction in 6MWD after receiving anthracycline-based chemotherapy. It was an analytical observational study with a retrospective cohort design that conducted on breast cancer patients underwent anthracycline-based chemotherapy. Subjects were patients from the Cardio-oncocare registry who met the inclusion and exclusion criteria. The CTRCD was assessed using left ventricle ejection fraction (LVEF) and global longitudinal strain (LVGLS) by transthoracic echocardiography examination based on criteria from the European Society of Cardiology guidelines. The 6MWD was assessed by performing 6-min walking tests. The LVEF, LVGLS and 6MWD data were retrieved from the Cardio-oncocare registry database, which were performed before and after chemotherapy. The changes and association of LVEF, LVGLS and 6MWD from before to end of chemotherapy were analyzed. Of 250 Cardio-oncocare registered patients, 58 patients met the criteria. Among them, 17 patients (29%) had CTRCD, and 41 patients (71%) had no CTRCD after chemotherapy. A significant decrease in LVEF and LVGLS in patients with CTRCD was observed. The 6MWD before chemotherapy did not statistically differ between CTRCD and no CTRCD patients. After chemotherapy, the proportion of patients experienced reduction of 6MWD was not significantly different between CTRCD patients and no CTRCD patients [7 patients (41%) vs. 21 patients (51%); p=0.342]. In conclusion, there is no significant association between CTRCD and reduction of 6MWD in breast cancer patients receiving antracycline-based chemotherapy.